Specificity Of Professional Ego - The Image Of Male And Female Leaders - Ladzina, Natalya; Akazhanova, Alma; Zeinolla, Saule; Nazyrova, Larissa; Nurgaliyeva, Ayzhan (Opción, 2019)
Article deals with a comparative analysis of various methodological approaches to ego-image and ego-concept of the leader, potential diagnostic methods of ego-image analysis and creation of a personal profile are proved. As a result, the real and ideal image of male leaders is typical for independent, sociable people with acceptance of fight. In the ideal image, there are differences in the decrease of indicators of dependence and avoidance of a fight. In conclusion, the prevalence of the cooperating and altruistic styles of the interpersonal relations reflects characteristics, which correspond with femininity in society.